Odpowiedź:
1) [tex]\frac{3p-8}{2} + 4 = \frac{2p+3}{4}[/tex]
[tex]\frac{3p-8}{2} + \frac{8}{2} = \frac{2p+3}{4}[/tex]
[tex]\frac{3p}{2} = \frac{2p+3}{4} / \cdot 4[/tex]
[tex]2\cdot 3p = 2p + 3[/tex]
[tex]6p = 2p + 3[/tex]
[tex]p = \frac{3}{4}[/tex]
2) [tex]3 - \frac{4r-9}{3} = \frac{r+2}{2}[/tex]
[tex]\frac{9}{3} - \frac{4r-9}{3} = \frac{r+2}{2}[/tex]
[tex]\frac{18-4r}{3} = \frac{r+2}{2} / \cdot 6[/tex]
[tex]2(18-4r) = 3(r+2)[/tex]
[tex]36-8r = 3r+6[/tex]
[tex]-11r = -30[/tex]
[tex]r = \frac{30}{11}[/tex]
3) [tex]2s-\frac{s+1}{5} = 3 - \frac{2s+3}{2}[/tex]
[tex]\frac{10s}{5} - \frac{s+1}{5} = \frac{6}{2} - \frac{2s+3}{2}[/tex]
[tex]\frac{9s-1}{5} = \frac{3-2s}{2} / \cdot 10[/tex]
[tex]2(9s-1) = 5(3-2s)[/tex]
[tex]18s-2 = 15-10s[/tex]
[tex]28s=17[/tex]
[tex]s=\frac{17}{28}[/tex]